Effective communication enhances the patients' endoscopy experience. (February 2016) - Toomey, D.; Hackett-Brennan, M.; Corrigan, G.; Singh, C.; Nessim, G.; Balfe, P.
Abstract Background Undergoing an endoscopy is a stressful experience for patients. Aims To audit the endoscopy pathway to improve patient satisfaction. Methods A prospective survey of endoscopy patients to identify system improvements that were then implemented. Results The survey was performed before (N  = 71) and after (N  = 60) process improvements identified by the initial survey. Information provision and staff communication skills were identified for optimisation. Patient anxiety at home was significantly reduced (median 2 vs. 1, p  < 0.01). Education of endoscopy staff significantly improved the quality of information provided before and after the procedure with regard to sedation (median 4 vs. 5, p  < 0.01), discomfort (median 4 vs. 5, p  < 0.01), complications (28 vs. 82 %, p  < 0.01), findings (89 vs. 100 %, p  < 0.01) and follow-up (73 vs. 90 %, p  = 0.015). Gloucester Comfort Scores during endoscopy improved (median 1 vs. 0, p  < 0.01) without increasing sedation levels. Patient feelings of invasion/trauma significantly decreased. Overall 95 % of patients were satisfied. Conclusion Structured information leaflets and improved staff communication skills reduce anxiety and enhance patients' experiences. They are now standard operating procedures.